Feasibility study of Using Liquid Gel in Stabilizing Doogh by Hydrocolloids of Psyllium Husk and Guar Gum - Tayebeh Tavakoli Vardanjani; Mohammad Hojjatoleslamy; Mohammad Ali Shariati (International Journal of Science and Engineering, 2014)
Liquid gel technology is a method that applies in stabilizing of suspension and dispersion of solid particles in beverages. Doogh which is an Iranian traditional and functional drink has allocated a unique position among consumers. Precipitation of hydrocolloids in Doogh has been always one of the most important challenge in producing this drink. Base of this fact, this study deals with using liquid gel technology (Guar gum and Hydrocolloids of  Psyllium Husk ) .Different hydrocolloids concentration (0.01, 0.03, 0.05 %w/w) in Doogh heated to be hydrated at 80 ˚C resulting in producing Gel. Their flow behavior, particle distribution and microstructure analyzed, phase separation also evaluated by measuring volume of separated phases .Guar remarkably effected on Doogh flow behavior and caused to a high apparent viscosity in low shear rates, changing microstructure therefore changing particles size as well. It also subtracted the volume of separated phase .Xanthan and Psyllium increased stability of Doogh by increasing more repulsive force between particles, however larger particles precipitated. Samples containing Guar Gum indicated more yield stress.